Low injury incidence and excellent return to sport after injuries in beach handball - a cross-sectional survey of 651 athletes - Degenhardt, H.; Hinz, M.; Rupp, M.-C.; Kleim, B. D.; Vieider, R. P.; Weyer, M.; Henze, A.-S.; Imhoff, A. B.; Siebenlist, S.; Ehmann, Y. J. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background To quantify the five-year injury incidence and to identify risk factors and common injury patterns in beach handball athletes. It was hypothesized that there would be a low incidence of injuries with identifiable risk and preventative factors.